2012
DOI: 10.1038/nsmb.2421
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic switch of the signal recognition particle from scanning to targeting

Abstract: Ribosomes synthesizing inner membrane proteins in Escherichia coli are targeted to the membrane by the signal recognition particle (SRP) pathway. By rapid kinetic analysis we show that after initial binding to the ribosome, SRP undergoes dynamic fluctuations in search of additional interactions. Non-translating ribosomes, or ribosomes synthesizing non-membrane proteins, do not provide these contacts, allowing SRPs to dissociate rapidly. A nascent peptide in the exit tunnel stabilizes SRPs in a standby state. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
109
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 69 publications
(125 citation statements)
references
References 32 publications
13
109
3
Order By: Relevance
“…Previous kinetic analyses revealed that, similar to what we report here for TF, SRP scans ribosomes rapidly until binding is stabilized on translating ribosomes that have their peptide exit tunnel filled ('stand-by') or expose a signal-anchor sequence ('targeting') 13 . Assuming an SRP concentration in vivo of 0.1 mM and diffusion-controlled binding, as observed in vitro 13 , the effective rate of SRP binding to ribosomes or RNCs is about 10 s À 1 .…”
Section: Kinetics Of Tf Interaction With Non-translating Ribosomesmentioning
confidence: 70%
See 4 more Smart Citations
“…Previous kinetic analyses revealed that, similar to what we report here for TF, SRP scans ribosomes rapidly until binding is stabilized on translating ribosomes that have their peptide exit tunnel filled ('stand-by') or expose a signal-anchor sequence ('targeting') 13 . Assuming an SRP concentration in vivo of 0.1 mM and diffusion-controlled binding, as observed in vitro 13 , the effective rate of SRP binding to ribosomes or RNCs is about 10 s À 1 .…”
Section: Kinetics Of Tf Interaction With Non-translating Ribosomesmentioning
confidence: 70%
“…Assuming an SRP concentration in vivo of 0.1 mM and diffusion-controlled binding, as observed in vitro 13 , the effective rate of SRP binding to ribosomes or RNCs is about 10 s À 1 . This rate matches the rate of TF dissociation from non-TF-substrate RNCs, Lep75-RNC in our experiments, which may optimize the access of SRP to its substrate RNCs.…”
Section: Kinetics Of Tf Interaction With Non-translating Ribosomesmentioning
confidence: 99%
See 3 more Smart Citations